The effect of rest interval length on upper and lower body exercises in resistance-trained females - Millender, D. J.; Mang, Z. A.; Beam, J. R.; Realzola, R. A.; Kravitz, L. (International Journal of Exercise Science, 2021)
The purpose of this study was to investigate the effects of SHORT (1 min) and LONG (3 min) rest intervals (RI) on total volume lifted (TVL), repetition performance, fatigue index (FI), and blood lactate [La] during upper body (chest press) and lower body (leg press) exercise with low-intensity (75% of a 10-RM) in trained female lifters. Fourteen females (mean ± SD, age = 22.9 ± 5.4 years, training experience = 5.2 ± 2.5 years, height = 166.1 ± 6.9 cm, weight = 61.3 ± 5.1 kg, body fat % = 21.7 ± 3.3%) participated in this randomized, repeated-measures, cross-over design study. They performed four sets to failure on chest press (CP) and leg press (LP) under two conditions (SHORT and LONG RIs) in a counterbalanced manner. Paired-samples t-tests were used to analyze mean differences for TVL in CP and LP, separately. A 2 (exercise) x 2 (rest interval) repeated measures ANOVA was used to analyze mean differences in FI and average [La] values. A 2 (rest interval) x 4 (sets) repeated measures ANOVA was used to analyze mean differences in repetitions completed for each exercise. TVL for SHORT was significantly less when compared to LONG for both exercises. There was no significant difference in average [La] between RIs despite a greater FI in SHORT compared to LONG for both exercises. Lastly, [La] was higher during LP compared to CP irrespective of RI length. These results suggest that longer RIs are better for female lifters who want to optimize TVL with low-intensity resistance training. Metabolic stress, as measured by blood lactate, was greater during lower-body exercise.